STUDY OF ENVIRONMENTAL CRIMINAL LAW FROM THE PERSPECTIVE OF CRIMINAL LAW IN INDONESIA - Sahrul Mukhlis Lubis; Muhammad Ilham; Abdul Rozak Lubis (PT. Radja Intercontinental Publishing, 2023)
The living environment is the unity of space with all the objects and living creatures in it, including humans and their behavior, which can influence the continuity of life between humans and the environment around them. At this time, environmental damage, especially in Indonesia, is increasingly worrying, which if left unchecked will gradually threaten human life itself. Apart from being caused by natural conditions, environmental damage is also generally caused by damage resulting from human activities that excessively exploit nature, such as forest destruction, illegal felling of trees, pollution of water, air, land and so on. This research examines the study of criminal law on the environment from the perspective of criminal law in Indonesia as well as the ambiguity of norms regarding the regulation of B3 waste dumping. This research uses a type of normative research which is then explained descriptively analytically with argumentative techniques. Indonesian positive law regulates the environment in Law No. 32 of 2009 concerning Environmental Protection and Management. It is hoped that future criminal law policies in dealing with environmental crimes from a criminal law perspective can be seen from various aspects such as criminalization policies, criminal responsibility. , criminal sanctions and punishment.